(3TQM bGfhf GdYbhHGJ (B:s (3GdbSe GdYGe (B= Explanation of the penal law : the general section /s - (3GdMdHj, eMeO Ydj GdSGde YjGOs; (3GdaGjR, CcQe WQGO,s 1973- ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2011)
(3jJfGhd cJGH (B((3TQM bGfhf GdYbhHGJ (B: (3GdbSe GdYGe(B) (3hGdPj bGe HJCdjag (B((3eMeO Ydj GdSGde GdMdHj(B) (3aj MhGdj (B(373) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3bGfhf GdYbhHGJ aj GdCQOf(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdLRA GdChd (B: (3GdfXQjI GdYGeI ddLQjeI, GdHGH GdChd (B: (3bGfhf GdYbhHGJ hMOhOg, GdaUd GdChd (B: (3GdJYQja HbGfhf GdYbhHGJ, GdaUd GdKGfj (B: (3bGfhf GdLRGA hMOhO JWHjbg, GdHGH GdKGfj (B: (3CfhGY GdLQjeI hCUfGagG hCQcGfgG, GdaUd GdChd (B: (3CfhGY GdLQjeI hCUfGagG, GdaUd GdKGfj (B: (3CQcGf GdLQjeI, GdLRA GdKGfj (B: (3GdfXQjI GdYGeI ddYbhHI, GdHGH GdChd (B: (3eGgjI GdYbhHI hJYQjagG hCgOGagG, GdaUd GdChd (B: (3eGgjI GdYbhHI, GdaUd GdKGfj (B: (3CgOGa GdYbhHI hJUfjagG (B... (3EdN(B.s
(3HHdjhLQGajI (B: (3UaMI (B371-373.s
Keywords: (3GdLQjeI hGdeLQehfs -- (3bhGfjf hJTQjYGJs -- (3GdCQOfs; (3bGfhf GdYbhHGJs -- (3GdCQOfs